PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK KELAS VII MTs NEGERI 3 PALU - Masna, Masna; Arda; Mirnawati (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This study seeks to investigate the impact of the discovery learning model on students' scientific literacy skills concerning the topics of temperature and heat expansion in the seventh grade at MTs Negeri 3 Palu. The research employs a quantitative methodology featuring a quasi-experimental design that utilizes pretest and posttest measures in non-equivalent control group design. Class VII A serves as the experimental group, while class VII C acts as the control group, with participants selected through purposive sampling. The assessment tools consist of a multiple-choice pretest and posttest, comprising a total of 15 items. Data were analyzed utilizing a paired samples t-test. The results indicate that the significance value for students' scientific literacy skills is 0.00 (2-tailed), which is lower than the 0.05 threshold. This suggests that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the discovery learning model significantly impacts seventh-grade students' scientific literacy skills on the topics of temperature and heat expansion at MTs Negeri 3 Palu.